Stock Valuation and Financial Performance of PT Indofood Sukses Makmur Tbk - Ruliff Harlan; Yunieta Anny Nainggolan (Integrasi Sains Media, 2025)
In recent years, external factors may have influenced the performance of PT Indofood Sukses Makmur Tbk (INDF). Unusual weather patterns have allegedly disrupted supply chains and caused volatility in global wheat prices. This led to a revenue decline in both the agribusiness and Bogasari segments during 2023 and 2024. These pressures and market sentiment led to a relatively low P/E ratio of 6.34 in early 2025. However, other business segments, such as Consumer Branded Products and Distribution, continue to grow strongly. This raises concerns that INDF's market price may not fully reflect its intrinsic value. This study aims to assess INDF's fundamental condition, estimate its intrinsic price, and provide recommendations for prospective investors. It begins with a macroeconomic assessment, Porter's Five Forces, industry market ratio comparison, financial ratio analysis, and absolute and relative valuation. The findings suggest that INDF has stable fundamentals and a competitive advantage. In addition, the valuation methods estimated that the intrinsic price of INDF shares is IDR 18,328. Compared to the market price of IDR 7,850, the potential upside could be 133.4%. This condition shows an opportunity for future price appreciation and thus is considered a good option for long-term investors.